Bioinformatics: Sequence, Structure and Databanks: A Practical Approach - D. Higgins (The practical approach series, 2003)
This volume covers practical important topics in the analysis of protein sequences and structures. It includes comparing amino acid sequences to structures comparing structures to each other, searching information on entire protein families as well as searching with single sequences, how to use the Internet and how to set up and use the SRS molecular biology database management system. Finally, there are chapters on multiple sequence alignment and protein secondary structure prediction. The book will be invaluable to occasional users of these techniques as well as experienced professionals or researchers.